Effects of online brain training on self‐reported mental health symptoms for generally healthy adults during the Covid‐19 pandemic - Sarah A. Laane; Lori G. Cook; Jeffrey S. Spence; Michelle N. Harris; Sandra Bond Chapman (Brain and Behavior, 2023)
Abstract Background The cognitive training Strategic Memory Advanced Reasoning Training (SMART) has been shown to improve symptoms of depression, anxiety, and stress when completed using in‐person delivery, but mental health outcomes have not yet been studied for online delivery of SMART. Methods Data was analyzed from 145 generally healthy adults participating in the BrainHealth Project pilot study who had access to 12 weeks of online self‐paced SMART and self‐reported mental health symptoms on the Depression Anxiety Stress Scale (DASS‐21) pre‐ and post‐training. We utilized linear models to examine the change in self‐reported symptoms of depression, anxiety, and stress following the 12‐week training period and to explore the influence of age, gender, and education on changes in symptomatology. Data from 44 participants who completed a follow‐up DASS‐21 6 months after completing SMART was used to explore the lasting impact of the training. Results Improvements in depression, anxiety, and stress symptoms were observed following online SMART, evidenced by a significant decrease in self‐reported symptoms on the DASS‐21. Improvement in self‐reported mental health symptomatology was maintained or continued to improve 6‐month post‐training. No significant effect of gender was observed, but findings motivate additional exploration of the effects of education and age. Conclusion Online SMART should be considered a low‐cost, high‐impact approach for supporting public mental health for generally healthy adults.